2009
DOI: 10.3748/wjg.15.961
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of gastroesophageal reflux disease in Qashqai migrating nomads, southern Iran

Abstract: AIM:To investigate the prevalence and risk factors of gastroesophageal reflux disease (GERD) symptoms in Qashqai migrating nomads with a different life style in Fars province, southern Iran. METHODS:In summer 2006, 748 Qashqai migrating nomads aged 25 years or more were enrolled using a multiple-stage stratified cluster random sampling method. A questionnaire consisting of demographic characteristics, lifestyle and GERD symptoms (heartburn, regurgitation, chest pain, dysphagia, hoarseness and cough) as complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
33
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 25 publications
(32 reference statements)
6
33
0
1
Order By: Relevance
“…Although smoking has been associated with increased frequency of acid reflux, its contribution to GERD and FD is still a matter of investigation because acid exposure accounts for only 4% of the variation in GERD symptoms [27,28]. Findings on the association between smoking and upper GI disorders are inconsistent [7,29,30,31,32,33,34,35]. Some epidemiological studies have suggested tobacco smoking as a risk factor for GERD and FD [22,36].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although smoking has been associated with increased frequency of acid reflux, its contribution to GERD and FD is still a matter of investigation because acid exposure accounts for only 4% of the variation in GERD symptoms [27,28]. Findings on the association between smoking and upper GI disorders are inconsistent [7,29,30,31,32,33,34,35]. Some epidemiological studies have suggested tobacco smoking as a risk factor for GERD and FD [22,36].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies have introduced smoking, among other unhealthy lifestyle factors, as a major contributing factor to upper GI disorders [7,17,18,19]. Some studies have suggested that the most important risk factor for GERD in Western countries is tobacco smoking [18,20,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is one of the highest values from the Far East countries (10). On the other hand, in a study conducted on the Qashqai area of Iran, the rate of patients having reflux episode once a week during the last year was found to be 33%, and it was specified that this value increased with age (11). The authors explained that the reason for this higher value in nomads than in settled people was the fact that nomads had different socioeconomic features educational status, and lifestyles.…”
Section: Turk J Gastroenterol 2017; 28(suppl 1): S4-s9mentioning
confidence: 99%
“…Recent studies show that the prevalence of GERD has increased up to 2 to 6 times in the last two decades (5). Research has shown that the prevalence of this disease in Iran is about 15%, which is higher than the average amount in Asia (7)(8)(9). Typical GERD symptoms include an uncomfortable sensation of heartburn under the sternum or regurgitation of gastric contents (1,10).…”
Section: Introductionmentioning
confidence: 99%